Drugs most commonly used in chronic antithrombotic therapy and their impact on patients preparing for maxillofacial surgery. - Sylwia Wójcik; Katarzyna Mocny-Pachońska; Michał Wójcik; Tadeusz Morawiec (Farmacja Polska, 2023)
Constant advances in treatment methods in all medical specialties have led to the development and introduction of new drugs into therapy. Antithrombotic drugs are increasingly prescribed in the chronic treatment of numerous medical conditions. This is a large group of medications that act on components of the clotting process. We can categorize the vast majority of antithrombotic drugs used in chronic therapy into antiplatelet drugs - which are inhibiting platelet activity, or into anticoagulants - which are affecting various factors of the clotting cascade. In recent years, thanks to advances in the prevention and treatment of various cardiovascular diseases, in daily clinical practice we can see patients taking a combination therapy of two such drugs chronically. Even triple antithrombotic therapy is used in secondary prevention and in patients with high thromboembolic risk. The use of the above-mentioned medications prevents the formation of embolisms, but may pose a risk of an excessive bleeding that threatens the life or health of the patient. Hemorrhagic complications of chronically used anticoagulants are a problem of particular importance in patients preparing for maxillofacial surgery. Within this field, we can distinguish, according to the recommendations of the International Society of Thrombosis and Hemostasis, procedures with a low or moderate risk of bleeding and those with a high risk of bleeding. For operations with a high risk of bleeding, careful preparation of the patient is necessary. The authors discuss the drugs most commonly used in antithrombotic therapy. They describe their types and their mode of action and pharmacological properties. In the following review paper, based on the current literature, recommendations relating to each of the above-mentioned groups of treatments are presented. The guidelines discussed in the paper will help safely prepare patients who chronically take antithrombotic drugs for various types of maxillofacial surgical procedures.